Determinants of Double-J Ureteral Stent Intolerance: Patient Susceptibility, Device Design, and Symptom-Modifying Strategies - Grabarczyk, Mikołaj; Kozłowski, Sebastian; Błaszczyk, Bartosz; Szczepańska, Weronika; Szychowska, Aleksandra; Smolińska, Ewa (Quality in Sport, 2026)
Double-J ureteral stents are widely used in contemporary urological practice to maintain urinary drainage and protect renal function in patients with obstructive, postoperative, benign, and malignant ureteral conditions. Despite their clinical utility, these devices are frequently associated with pain, lower urinary tract symptoms, sexual discomfort, reduced physical activity, impaired work performance, and deterioration of quality of life. This narrative review summarizes current evidence on determinants of Double-J stent intolerance. Available data indicate that stent-related symptoms are not determined solely by the presence of a foreign body in the urinary tract, but rather by a multidimensional interaction between individual pain susceptibility, psychological phenotype, baseline urinary and pain symptoms, clinical context, microbiological factors, stent material, device geometry, indwelling time, and pharmacological management. Chronic pain conditions, depressive symptoms, anxiety, pain catastrophizing, central sensitization, younger age, higher body mass index, pre-existing urinary symptoms, stone burden, and bilateral disease may increase the risk of poor tolerance. Modifiable device-related factors include excessive intravesical stent length, distal coil crossing the bladder midline, incomplete distal curl, larger diameter, greater stiffness, and conventional designs with substantial bladder material. Softer and smaller-diameter stents, optimized stent positioning, complete intraureteral designs, pigtail-suture stents, and antireflux stents may reduce selected symptom domains. Pharmacological strategies, including alpha-blockers, antimuscarinics, beta-3 agonists, and pregabalin, should be tailored to the dominant symptom profile. A personalized approach integrating preoperative risk stratification, careful device selection, optimized dwell time, and targeted pharmacotherapy may improve stent tolerance and support better clinical decision-making.